2023
DOI: 10.3389/fendo.2023.1142177
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic significance of main metabolic risk factors in primary biliary cholangitis: a retrospective cohort study of 789 patients

Dan-Tong Zhao,
Hui-Ping Yan,
Ying Han
et al.

Abstract: BackgroundMetabolic risk factors in primary biliary cholangitis (PBC) have not been well described in China. Additionally, it is unclear whether these factors have an impact on the prognosis of PBC patients. Therefore, this study aimed to investigate the prevalence of main metabolic risk factors in PBC, and to evaluate their prognostic values for liver-related outcomes.MethodsA cohort of 789 PBC patients was retrospectively studied between July 2008 and September 2019 by investigating the main metabolic risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Among the other illnesses potentially heightening the overall cardiovascular risk factors in PBC subjects, we can find hypertension and T2DM (besides dyslipidemia, as already indicated in the paragraph above), with hypertension playing an apparently significant role in worsening these patients' outcomes; in particular, anti-sp100 antibodies considered specific for PBC were found associated with adverse outcomes in PBC subjects [77].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Among the other illnesses potentially heightening the overall cardiovascular risk factors in PBC subjects, we can find hypertension and T2DM (besides dyslipidemia, as already indicated in the paragraph above), with hypertension playing an apparently significant role in worsening these patients' outcomes; in particular, anti-sp100 antibodies considered specific for PBC were found associated with adverse outcomes in PBC subjects [77].…”
Section: Discussionmentioning
confidence: 64%
“…There are many commonalities between MASLD and acute cholangitis: the latter is also associated with T2DM and insulin resistance [75], obesity (which is, in turn, strongly predisposes individuals to the formation of gallstones) [76], and intestinal dysbiosis (understood as an imbalance of intestinal bacterial flora) [77]. The most likely hypothesis is that primary bacteremia of the presumed gastrointestinal origin in MAFLD patients, supporting the role of the gut-liver axis [78], can be associated with the low-grade inflammation generated chronically in the liver condition (MASLD) and may somehow predispose individuals to inflammation in the small-and medium-sized bile ducts.…”
Section: Masld and Acute Biliary Diseasementioning
confidence: 99%
“…Diabetes has a long history of causing liver damage. In a retrospective cohort study in China, T2DM was found to be one of the major metabolic risk factors for PBC, with 11.9% of patients with T2DM having lower albumin, platelet counts and a higher rate of cirrhosis than non-T2DM patients; however, 54.3% of these patients also had hyperlipidemia, hypertension and NAFLD ( 9 ), which caused some interference in the study. In the most recent years, several epidemiologic studies have demonstrated a strong correlation between DM and autoimmune liver disease.…”
Section: Introductionmentioning
confidence: 99%